Strengthening Inclusive Education through CSR-Based Community Service Programs: Enhancing Teacher Capacity and School Accessibility - Imam Yuwono; Utomo Utomo; Mirnawati Mirnawati; Rina Hadiastuti (Carmin: Journal of Community Service, 2026)
This community service (PkM) program aims to strengthen the implementation of inclusive education through Corporate Social Responsibility (CSR) support from PT. Indobara. The target partners of this program are teachers and inclusive schools that face limitations in capacity, accessibility, and collaboration in supporting students with special needs. The program was implemented using a participatory approach through several stages, including problem identification and needs assessment with partners, program design based on partner needs, implementation through training and mentoring, and evaluation of outcomes and impacts. The results of the program indicate significant improvements in teachers’ competencies in inclusive teaching practices, increased school accessibility, and strengthened collaboration between schools, PT. Indobara, and the community. These outcomes reflect measurable changes in partner capacity and the learning environment. In conclusion, this PkM activity demonstrates that CSR-based interventions can effectively support inclusive education when implemented collaboratively and sustainably. The impacts of this program include improved quality of inclusive learning, increased awareness and commitment among stakeholders, and the establishment of sustainable school industry partnerships that can be adapted and replicated in other contexts.